2015
DOI: 10.1007/s11434-015-0902-0
|View full text |Cite
|
Sign up to set email alerts
|

Magnetogenetics: remote non-invasive magnetic activation of neuronal activity with a magnetoreceptor

Abstract: Current neuromodulation techniques such as optogenetics and deep-brain stimulation are transforming basic and translational neuroscience. These two neuromodulation approaches are, however, invasive since surgical implantation of an optical fiber or wire electrode is required. Here, we have invented a non-invasive magnetogenetics that combines the genetic targeting of a magnetoreceptor with remote magnetic stimulation. The non-invasive activation of neurons was achieved by neuronal expression of an exogenous ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 55 publications
1
76
3
Order By: Relevance
“…Also, the identified mechanoelectrical effects are dominant in the short time scales considered here, but in conjunction with parallel thermal effects like changes in the Q 10 factor [47], probably play a significant role under a wide array of thermal modulation scenarios [48]. Related insights may also help guide our understanding of other emerging neurophysical modalities like magnetogenetic stimulation (whose biophysics is still poorly understood [49,50]). For example, we note that membrane mechanoelectrical effects involving dimensional changes were suggested in other contexts involving changes in intramembranal forces, including action potential-related intramembrane thickness variations [51][52][53] and ultrasoundinduced formation of intramembrane cavities (or "bilayer sonophores" [54]).…”
Section: Discussionmentioning
confidence: 72%
“…Also, the identified mechanoelectrical effects are dominant in the short time scales considered here, but in conjunction with parallel thermal effects like changes in the Q 10 factor [47], probably play a significant role under a wide array of thermal modulation scenarios [48]. Related insights may also help guide our understanding of other emerging neurophysical modalities like magnetogenetic stimulation (whose biophysics is still poorly understood [49,50]). For example, we note that membrane mechanoelectrical effects involving dimensional changes were suggested in other contexts involving changes in intramembranal forces, including action potential-related intramembrane thickness variations [51][52][53] and ultrasoundinduced formation of intramembrane cavities (or "bilayer sonophores" [54]).…”
Section: Discussionmentioning
confidence: 72%
“…Besides, Xie's group has reported the co-purification of MAGR and CRY2 in human (Qin et al, 2016). Therefore, using medaka as a vertebrate model for magnet biology will not only boost our knowledge of animal MR but also cast light on understanding human MR. On the other hand, magnetogenetics that combine the genetic targeting of MagR with remote magnetic stimulation has been developed as a promising method for non-invasive neuron stimulation, which might replace the invasive approaches such as optogenetics and deep-brain stimulation in neurobiology research (Long et al, 2015). Thus, our study of medaka magnet biology could provide a good model and help advance the technology of magnetogenetics.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in neuroscience, magnetogenetics was recently reported as a promising noninvasive technique to control gene expression and cellular activity in vivo (Etoc et al, 2013;Etoc et al, 2015;Long et al, 2015;Stanley et al, 2015;Stanley et al, 2016;Wheeler et al, 2016). It shows many advantages over the currently widely used techniques such as deep-brain stimulation and optogenetics (Wichmann and Delong, 2006;Zhang et al, 2011), which require surgical implantation of a wire electrode or optical fiber (Kringelbach et al, 2007;HĂ€usser, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has demonstrated that overexpressing the protein ferritin allows for the intracellular synthesis of magnetic nanoparticles; when ferritin is fused to a TRPV channel, the resulting particles allow for radio and magnetic activation of that channel [55,56]. In addition, the recent discovery of a new candidate magnetoreceptor MagR, an iron-sulfur cluster-binding protein that creates a rodlike complex with the cryptochrome Cry, motivates the possibility of a new family of fully genetically-encoded magnetogenetic tools [57, 58]. …”
Section: Magnetically Inducible Toolsmentioning
confidence: 99%